Save me [large type] - Scottoline, Lisa (Thorndike Press, 2011)
When an explosion rips through the nearly empty cafeteria of an elementary school, Rose leads two girls to safety before racing to rescue her own daughter, Melly. But Rose soon learns that she may face both civil and criminal charges for her heroics because one of the girls she saved was seriously injured in the resulting fire that killed three school staff members. Media demands, legal maneuvering, and social pressures create tension, and dark secrets from the town's past-- and from Rose's-- are revealed.